1998
DOI: 10.1359/jbmr.1998.13.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Stretch Enhances Gap Junctional Communication Between Osteoblastic Cells

Abstract: Mechanical loading is essential to maintain skeletal integrity. Because gap junctions in bone are affected by mechanical factors, we studied whether stretch, an anabolic stimulus for osteoblasts, modulates direct intercellular communication in these cells. Gap junctional communication during stretch was assessed using a newly developed method, the "parachute assay," which allows monitoring of dye diffusion without disruption of the plasma membrane. Application of cyclic stretch for 2 or 24 h to well-coupled RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
127
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(128 citation statements)
references
References 49 publications
1
127
0
Order By: Relevance
“…The initial response to flow may derive from activation of a non-cAMP pathway. Stretch also increases gap junctional communication in osteoblasts through changing connexin-43 function: cyclic stretch increased dye diffusion (Ziambaras et al, 1998). Whether this latter effect required PGE 2 release is not known.…”
Section: Signaling Through G-proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial response to flow may derive from activation of a non-cAMP pathway. Stretch also increases gap junctional communication in osteoblasts through changing connexin-43 function: cyclic stretch increased dye diffusion (Ziambaras et al, 1998). Whether this latter effect required PGE 2 release is not known.…”
Section: Signaling Through G-proteinsmentioning
confidence: 99%
“…extracellular signal-regulated kinase MAPK mitogen-activated protein kinase Osteopontin (You et al, 2001) (Toma et al, 1997;Ziambaras et al, 1998) Collagenase-3 (Yang et al, 2004) Gene. Author manuscript; available in PMC 2013 June 20.…”
Section: Abbreviationsmentioning
confidence: 99%
“…These conditional Cx43 knockout mice, which use a 2.3-kb collagen I promoter-driven Cre-recombinase to excise a floxed Cx43 allele in cells of the osteoblast lineage, exhibit severe osteopenia as a result of defective osteoblast function. Further, the skeletons of these animals have been shown to be refractory to the anabolic effects of intermittent PTH administration, indicating a critical role of Cx43 in coordinating cell function in response to anabolic cues.Relatively little is known about the precise molecular role of gap junctions in sensing and responding to biological cues during bone formation, though in the past decade critical insights have been gained into the importance of gap junctions in processes such as response to growth factors and hormones (Schiller et al, 1992;Chiba et al, 1994;Van der Molen et al, 1996;Civitelli et al, 1998;Schiller et al, 2001), mechanical load (Jorgensen et al, 1997(Jorgensen et al, , 2000Ziambaras et al, 1998;Romanello and D'Andrea, 2001;Saunders et al, 2001Saunders et al, , 2003Cherian et al, 2003Cherian et al, , 2005Taylor et al, 2007), bisphosphonates (Plotkin et al, 2002(Plotkin et al, , 2005, and interaction with other cells (Villars et al, 2002). Importantly, less still is known regarding the biologically relevant second messengers that osteoblast and osteocyte gap junctions communicate among cells, and many molecular mechanisms have yet to be deduced.…”
mentioning
confidence: 99%
“…For instance, gap junction-deficient cells are dramatically less responsive to diverse extracellular signals including PTH, 47 and especially relevant to this review, fluid flow 48,49 and electric fields, 50 than are wild-type osteoblastic cells. Furthermore, cyclic stretch has been shown to increase connexin 43 expression and gap junctional intercellular communication in osteoblastic cells in vitro, 51 and several groups [52][53][54][55] have demonstrated that fluid flow increases gap junction expression and function in osteocytic MLO-Y4 cells. In vivo, Lozupone et al 56 demonstrated that mechanical loading of rat metatarsal bones increased the incidence of osteocytic gap junctions, and Su et al 57 demonstrated that expression of connexin 43 by osteocytes is increased in areas of bone exposed to tension relative to areas exposed to compression or to control bone.…”
Section: Putative Mechanosensorsmentioning
confidence: 98%